The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1116/1.590893
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of chemically vapor deposited TiN films prepared using tetrakis-ethylmethyl-amido-titanium

Abstract: Articles you may be interested inIn situ physical vapor deposition of ionized Ti and TiN thin films using hollow cathode magnetron plasma source Investigation on multilayered chemical vapor deposited Ti/TiN films as the diffusion barriers in Cu and Al metallization J.Low pressure chemical vapor deposition of TiN was studied with tetrakis-ethylmethyl-amido titanium ͑TEMAT͒ in a cold-wall-type vertical flow reactor with helium or ammonia. Thermal decomposition of the precursor under helium atmosphere yielded TiN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
3
10
0
2
Order By: Relevance
“…High carbon content (from 25 to 35 at. % in these experiments, as confirmed by Auger electron spectroscopy, AES) is consistent with the previous studies. , The AES studies also confirmed the absence of silicon in the topmost layers, which suggests that the film produced is continuous. The thickness of the carbonitride layer was estimated to be ∼10 nm on the basis of the ex situ time-of-flight secondary ion mass spectrometry and atomic force microscopy (AFM) studies performed at the Surface Analysis Facility at the University of Delaware.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…High carbon content (from 25 to 35 at. % in these experiments, as confirmed by Auger electron spectroscopy, AES) is consistent with the previous studies. , The AES studies also confirmed the absence of silicon in the topmost layers, which suggests that the film produced is continuous. The thickness of the carbonitride layer was estimated to be ∼10 nm on the basis of the ex situ time-of-flight secondary ion mass spectrometry and atomic force microscopy (AFM) studies performed at the Surface Analysis Facility at the University of Delaware.…”
supporting
confidence: 91%
“…The root-mean-square roughness of this film was estimated to be ∼3-nm on the basis of AFM studies. Previous studies of TiCN films deposited from tetrakis(dialkylamino)titanium precursors at conditions similar to ours suggest that these films have amorphous structure, which is one of the main reasons why this approach leads to better conformal filling and a smoother surface than in the case of titanium nitride or titanium carbonitride with a low carbon content . The detailed structure of the films produced by such an approach in our studies is the subject of a separate publication…”
supporting
confidence: 67%
“…In the vast majority of devices, copper is separated from a semiconductor surface by a diffusion barrier material. One of the most prominent materials, possessing high thermal stability, good diffusion barrier properties, and low electrical resistivity is titanium nitride, TiN. This material can be deposited on a semiconductor substrate using such chemical vapor deposition precursors as dialkyl-amino derivatives (Ti[NR 2 ] 4 , where R = Me, Et) and TiCl 4 , used in combination with NH 3 and sometimes H 2 ; however, the latter method often presents significant problems associated with chlorine contamination and formation of NH 4 Cl. The chemical and physical properties of TiN films can be controlled by manipulating the carbon content, and in fact, titanium carbonitride films, TiC x N y , have been shown to have a set of very attractive physical properties, including better conformal filling than titanium nitride. …”
Section: Introductionmentioning
confidence: 99%
“…deposition temperatures by CVD using metal-organic precursors such as tetrakis-dimethylamido-titanium (TDMAT) and tetrakisdiethylamido-titanium (TDEAT) [9]. However, the low deposition temperature (commonly less than 600 • C) has been found to yield poor crystallinity and low deposition rate (R dep ) [10,11], which is unattractive for the applications to high-speed cutting tools.…”
Section: Introductionmentioning
confidence: 98%